18F-FDG PET cannot predict expression of clinically relevant histopathological biomarkers in head and neck squamous cell carcinoma: a meta-analysis. (February 2022) - Surov, Alexey; Pech, Maciej; Eckert, Alexander; Arens, Christoph; Grosser, Oliver; Wienke, Andreas
Background: Head and neck squamous cell carcinoma (HNSCC) is a common cancer. Positron emission tomography (PET) with 18F-fluorodeoxyglucose (18F-FDG) is a widely used imaging modality in HNSCC. Purpose: To provide evident data about associations between 18F-FDG PET and histopathology in HNSCC. Material and Methods: The MEDLINE database was screened for associations between maximum standard uptake values (SUVmax ) derived from 18F-FDG PET and histopathological features in HNSCC up to May 2020. Only papers containing correlation coefficients between SUVmax and histopathology were acquired. Overall, 23 publications were collected. Results: The following correlations were calculated: KI 67: 12 studies (345 patients), pooled correlation coefficient (PCC): 0.23 (95% confidence interval [CI] 0.06–0.40); hypoxia-inducible factor-1α: eight studies (240 patients), PCC: 0.24 (95% CI 0.06–0.42); microvessel density: three studies (64 patients), PCC: 0.33 (95% CI 0.02–0.65); vascular endothelial growth factor: two studies (59 cases), PCC: 0.27 (95% CI 0.02–0.51); tumor suppressor protein p53: four studies (159 patients), PCC: 0.05 (95% CI –0.41 to 0.51); epidermal growth factor receptor: two studies (124 patients), PCC: 0.21 (95% CI 0.05–0.37); tumor cell count: three studies (67 patients), PCC: 0.18 (95% CI –0.06 to 0.42); tumor cell apoptosis: two studies (40 patients), PCC: 0.07 (95% CI = –0.85 to 0.99); B-cell lymphoma-2 protein: two studies (118 patients); PCC: 0.04 (95% CI –0.65 to 0.74); glucose-transporter 1: 10 studies (317 patients), PCC: 0.20 (95% CI 0.10–0.30). Conclusion: SUVmax derived from 18F-FDG PET cannot reflect relevant histopathological features in HNSCC.